2021
DOI: 10.1016/j.jhep.2021.06.036
|View full text |Cite
|
Sign up to set email alerts
|

24-Norursodeoxycholic acid reshapes immunometabolism in CD8+ T cells and alleviates hepatic inflammation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…However, by focusing on TH17 cells we further identified that through restricting glutaminolysis NorUDCA inhibits mTORC1 activity which is directly controlled by α-Ketoglutarate, a key metabolic intermediate biosynthesized along the glutaminolysis cascade (figure 7). Revisiting the mass spectrometry data set of NorUDCA-treated CD8 + T cells published in our previous study [11], we found that in accordance with our observation in TH17 cells the abundance of glutaminolysis rate-limiting enzyme GLS2 (Glutaminase 2) was also reduced. This suggests that GLS2 might be a potential metabolic checkpoint for NorUDCA's modulatory actions of glutamine metabolism in adaptive immune cells, thus provides an interesting direction for future investigations.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, by focusing on TH17 cells we further identified that through restricting glutaminolysis NorUDCA inhibits mTORC1 activity which is directly controlled by α-Ketoglutarate, a key metabolic intermediate biosynthesized along the glutaminolysis cascade (figure 7). Revisiting the mass spectrometry data set of NorUDCA-treated CD8 + T cells published in our previous study [11], we found that in accordance with our observation in TH17 cells the abundance of glutaminolysis rate-limiting enzyme GLS2 (Glutaminase 2) was also reduced. This suggests that GLS2 might be a potential metabolic checkpoint for NorUDCA's modulatory actions of glutamine metabolism in adaptive immune cells, thus provides an interesting direction for future investigations.…”
Section: Discussionsupporting
confidence: 90%
“…Cell surface and intracellular FACS stains for ex vivo isolated immune cells were performed at 4°C for 30min as previously described [11] using antibodies listed in Supplementary table 1. Intracellular staining of cytokines and transcription factors of in vitro cultured T H 17 cells was performed as described in [11].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations